Architectural Design of a Multichannel Porous Carbon Fiber for Efficient Electromagnetic Microwave Absorption - Cui, Wen-Qi (Langmuir : the ACS journal of surfaces and colloids, 2024)
An ingenious microstructure of electromagnetic microwave absorption materials is crucial to achieve strong absorption and a broad bandwidth. Herein, one-dimensional (1D) carbon fibers with implantation of zero-dimensional (0D) ZIF-8-derived carbon frameworks and construction of a three-dimensional (3D) microcosmic multichannel porous structure are fabricated by electro-blown spinning, solvent-thermal reaction, and high-temperature pyrolysis techniques. The 1D carbon fiber skeleton with a multichannel structure provides a direct axial conductive pathway for charge transport, which plays an important role in dielectric loss. The 0D surface carbon frameworks offer plenty of heterogeneous interfaces to trigger intensive interfacial polarization loss and act as dihedral angles for microwave scattering. The 3D microcosmic multichannel pores can not only generate multiple reflections as much as possible to dissipate electromagnetic microwave energy but also supply huge interior cavities to improve impedance matching. Thanks to the synergistic effect of a strong electrically conductive pathway for enhancing the conductive loss, a plenteous heterogeneous interface for triggering intensive interfacial polarization loss, microcosmic multichannel pores for generating multiple reflections and improving impedance matching, and N and O atom doping for inducing dipole polarization, the optimal sample with an ingenious microstructure delivers an excellent absorption performance of a minimum reflection loss of -35.5 dB at a thickness of 5.0 mm and an effective absorption bandwidth of 6.72 GHz (10.96-17.68 GHz) at a thickness of 2.0 mm. Such a well-designed multichannel porous carbon fiber may pave the way for the exploitation of high-performance microwave absorbing materials